Associations between exposure to electronic media and communication during early childhood: an integrative review - Gago Galvagno, Lucas G.; Azzollini, Susana C.; Elgier, Ángel M. (Pensando Psicología, 2022)
Purpose: to evaluate the amount of average use that infants make of electronic media, and to observe how it is associated with early childhood communication through an integrative review of the last 10 years (2010-2020). Topic: screen use during early childhood and its associations with verbal and pre-verbal communication skills. Development: verbal and non-verbal communication in the early years are essential skills, since they predict the later development of other cognitive skills and academic performance. Given that exposure to technological devices has increased in recent years, both in adults and in early childhood, it becomes important to review studies on this subject. We found 15 studies that met the inclusion criteria. In the first three years of life, on average the use of technological devices was 1 to 3 hours a day, they were negatively associated with the development of communication. However, it is necessary to take into account whether the activity is accompanied by an adult, the educational level, and the type of content that is consumed. Conclusions: it is necessary to carry out more research in the Latin American context, taking into account the diversity of electronic devices and content that we currently have.